Incarceration and Crime: Evidence from California's Public Safety Realignment Reform - Magnus Lofstrom; Steven Raphael (Institute for the Study of Labor (IZA), 2013)
We evaluate the effect of perhaps the largest exogenous decline in a state's incarceration rate in U.S. history on local crime rates. We assess the effects of a recent reform in California that caused a sharp and permanent reduction in the state's incarceration rate. We exploit the large variation across California counties in the effect of this reform on county-specific prison incarceration rates. We find very little evidence of an effect of the large reduction in incarceration rates on violent crime and evidence of modest effects on property crime, auto theft in particular. These effects are considerably smaller than existing estimates in the literature based on panel data for periods of time when the U.S. incarceration rate was considerably lower. We corroborate theses cross-county results with a synthetic-cohort analysis of state crime rates in California. This state-wide analysis confirms our findings from the county-level analysis. In conjunction with existing published research, the results from this study support the hypothesis of a crime-prison effect that diminishes with the scale of incarceration.
Keywords: K40; K42; H11; 330; crime; incapacitation; incarceration; prison; realignment; reform